USAHA KERIPIK SINGKONG DAPAT MENINGKATKAN EKONOMI KELUARGA (Studi Kasus: Kelurahan Sulamadaha, Kecamatan Ternate Barat Kota Ternate) - Tuara, Narilah A (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
This research was conducted with the aim of analyzing the income from cassava chips businesses to improve the family economy in Sulamadaha sub-district and to determine the contribution of cassava chips entrepreneurs' income to family economic income in Sulamadaha sub-district. This research uses case study research with a sample of 10 respondents. Primary data was obtained by interviewing respondents directly. The data analysis used is descriptive analysis to analyze the income and contribution of cassava chips entrepreneurs in increasing family income. The research results show that: (1) based on research results, housewives (wives) as cassava chips entrepreneurs contribute an average of Rp. 1,569,189 per month to total family income. (2) Based on the research results, the average monthly income of husbands is IDR. 2,503,333 per month. So the contribution of housewives is 45%, so the contribution of cassava chips to improving the family economy is very large. Logically speaking, the percentage income of 45% of the total family income is a large amount of income.